Contract cheating in higher education: a systematic literature review and future research agenda. Issue 4 (11th May 2022) - Ahsan, Kamrul; Akbar, Suraiyah; Kam, Booi
Abstract: Contract cheating is an increasingly challenging problem facing the higher education sector. This study assesses the current state of contract cheating research from various methodological and empirical perspectives. Through a systematic literature review of 51 peer-reviewed articles on contract cheating in higher education, we identify clusters of keywords, research trends and major research themes. Our analysis shows that theory-based research and studies using methodologies such as case study are lacking. We consolidate the research findings, presenting them in a conceptual framework to address contract cheating in higher education. Promising areas for future research on contract cheating in higher education are identified.